PENGGUNAAN METODE PEMBELAJARAN ROLE PLAYING TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI SD 06 METRO TIMUR - Arista Wati; Lian Ferliana; Nanda Febri Aryani; Anita Lisdiana (JEE (Jurnal Edukasi Ekobis), 2019)
The purpose of this study was to determine the improvement in student learning outcomes of grade VI at Elementary School 06 Metro Timur by using the role playing learning method in Social Studies subject with ASEAN material. The form of research used is Classroom Action Research. The research method used is a qualitative method wich is then interpreted with quantitative data (tests) as a basing for describing the succes of the implementation of learning that has been determined. Data collection techniques in the form of tests and observation sheets in the form of student activities. The results showed the average value of students before using the role playing learning method that is equal to 70,08 which is significantly different from the average value of students after using the role playing learning method that is equal to 91,04. So it can be concluded that the use of role playing learning methods can improve the learning outcomes of grade VI students in Social Studies at Elementary School Negeri 06 Metro Timur.Keyword: Role Playing Learning Methods, Social Studies Learning.